2014
DOI: 10.3329/bjsr.v26i1-2.20236
|View full text |Cite
|
Sign up to set email alerts
|

Yield response of a mustard mutant variety to different times of irrigation

Abstract: not available DOI: http://dx.doi.org/10.3329/bjsr.v26i1-2.20236 Bangladesh J. Sci. Res. 26(1-2): 89-93, December-2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…There was no statistical difference between treatment T 6 and T 4 in terms of yield. This result was in agreement with Akanda et al (1996), AICRP-RM (1999) and Mila et al (2013). They found that three irrigations were appropriate to get the potential yield of mustard.…”
supporting
confidence: 91%
“…There was no statistical difference between treatment T 6 and T 4 in terms of yield. This result was in agreement with Akanda et al (1996), AICRP-RM (1999) and Mila et al (2013). They found that three irrigations were appropriate to get the potential yield of mustard.…”
supporting
confidence: 91%
“…1). Mila et al (2013) (Table 3). Treatment T4 again produced the highest straw yield (4.46 t ha -1 ) and T1 produced the lowest yield (2.99 t ha -1 ), suggesting that straw yield of mustard decreased due to the water stress condition in control treatment.…”
Section: Effect Of Irrigation Treatmentsmentioning
confidence: 99%
“…The highest water use efficiency (0.48 t ha ). Mila et al (2013) reported that for application of two irrigations the yield of mustard increased, but the water use efficiency decreased.…”
Section: Water Use Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…is cultivated in almost 0.6 million acres of land with the average yield of 371 kg/acre, producing a total of 222 thousand metric tons in Bangladesh (BBS, 2014). This average yield of Brassica in Bangladesh is, however, very low compared to the many mustard growing countries of the world (Ara et al, 2014;Mila et al, 2014).…”
Section: Introductionmentioning
confidence: 99%